Division model of team-building alternatives for IT-companies - Мельник, Ольга Григорівна; Шпак, Юрій Несторович (Technology audit and production reserves, 2015)
The article argues priority of IT-industry development, the necessity of systematic consecutive team-building processes for IT-companies to maintain a high level of orders. It is established that the most appropriate option of IT-team selection is division- integrated approach using a combination of administrative, loyal indicator and the indicator of maximum benefits for IT-company. The model of gradual selection of personnel, not used in other projects, for IT-project vacancies is presented. The phases taking place in each new created team to achieve a coherent, effective and mutually agreed work with a high level of productivity are discussed. The peculiarities of each stage are characterized and advisability of team-building to facilitate exit from crisis stages is substantiated.